The Saving Behavior of State Vocational High School Students in Tegal Regency - Puspasari, Elsa; Yanto, Heri; Prihandono, Dorojatun (Universitas Negeri Semarang, 2018)
The country's savings growth rate is important to be improved so as to encourage economic growth of a nation. For this reason, supports from various parties are needed to improve people's behavior in saving. This study aims to analyze and identify the saving behavior of students of State Vocational Schools in Tegal Regency. Financial literacy, family environment, attitude to behavior, subjective norms, perceived behavioral control, and behavioral intentions are used to measure students' saving behavior. This study uses a quantitative approach. The population of the study is 1,520 students and the sample is 317 students. The number of samples is determined using the Slovin formula, while the sampling technique used is proportional random sampling. The technique of collecting data uses questionnaires. While the data analysis techniques used are descriptive analysis and path analysis. The results of path analysis show financial literacy and family environment directly influence attitude behavior, subjective norms, behavioral control, and behavioral intention. However, the family environment does not directly affect the behavioral intention. financial literacy and family environment have an Indirect influence on saving behavior through subjective norms, perceived behavioral control and behavioral intention.